2009
DOI: 10.1007/s00213-009-1489-4
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine withdrawal, acute effects, tolerance, and absence of net beneficial effects of chronic administration: cerebral blood flow velocity, quantitative EEG, and subjective effects

Abstract: Rationale Although the subjective effects of caffeine abstinence, acute and chronic administration, and tolerance are well described, the corresponding neurophysiological effects are not. Objectives Caffeine withdrawal, acute caffeine effects, caffeine tolerance, and net beneficial effects of chronic caffeine administration were investigated using cerebral blood flow velocity, quantitative EEG and subjective effects. Methods Sixteen regular caffeine users participated in this double-blind, within-subject s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 31 publications
4
50
0
Order By: Relevance
“…If caffeine was consumed, the adverse effects of lowered alertness and headache were avoided, but even after 100 + 150 mg of caffeine their alertness was not raised above the level of alertness showed by nonconsumers of caffeine (group N) who received placebo (Figure 1, middle panel). This result is similar to that from an early study comparing responses to caffeine of coffee drinkers and abstainers (Goldstein et al, 1969), and is consistent with the claim, supported by a variety of subsequent findings, that regular caffeine consumption provides little or no net benefit for alertness or performance on tests of vigilance (James and Rogers, 2005;Sigmon et al, 2009). Another interpretation could be that frequent caffeine consumers are 'constitutionally' less alert or more fatigued, and they use caffeine to remedy this state of affairs.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…If caffeine was consumed, the adverse effects of lowered alertness and headache were avoided, but even after 100 + 150 mg of caffeine their alertness was not raised above the level of alertness showed by nonconsumers of caffeine (group N) who received placebo (Figure 1, middle panel). This result is similar to that from an early study comparing responses to caffeine of coffee drinkers and abstainers (Goldstein et al, 1969), and is consistent with the claim, supported by a variety of subsequent findings, that regular caffeine consumption provides little or no net benefit for alertness or performance on tests of vigilance (James and Rogers, 2005;Sigmon et al, 2009). Another interpretation could be that frequent caffeine consumers are 'constitutionally' less alert or more fatigued, and they use caffeine to remedy this state of affairs.…”
Section: Discussionsupporting
confidence: 85%
“…However, although frequent consumers feel alerted by caffeine, especially by their morning tea, coffee, or other caffeine-containing drink, evidence suggests that this is actually merely the reversal of the fatiguing effects of acute caffeine withdrawal (James and Rogers, 2005;Sigmon et al, 2009). That is, little or perhaps no net benefit for alertness is gained.…”
Section: Introductionmentioning
confidence: 99%
“…Methodologies have included PET (Cameron, Modell, & Hariharan, 1990), Trans-cranial Doppler (Jones, Herning, Cadet, & Griffiths, 2000;Sigmon, Herning, Better, Cadet, & Griffiths, 2009) and MRI Perthen ). The current study utilised NIRS to confirm the previous observation of caffeine related reductions in CBF and this gave the added advantage of continuous recording from pre-dose until 66 minutes post-dose.…”
Section: Discussionmentioning
confidence: 85%
“…This has been seen in the modulation of putative indices of CBF using a number of methodologies. These include Positron Emission Tomography (PET) (Cameron, Modell, & Hariharan, 1990); Xenon Clearance (Lunt, Ragab, Birch, Schley, & Jenkinson, 2004), Trans-cranial Doppler (Jones, Herning, Cadet, & Griffiths, 2000;Sigmon, Herning, Better, Cadet, & Griffiths, 2009) and Magnetic Resonance Imaging (MRI) . With regards the latter method, Field et al (2003), using quantitative perfusion MRI undertaken approximately 60 to 90 minutes postdose of placebo or caffeine, found that habitual high consumers (>300mg/day) had greater placebo CBF in comparison to lower consumers (<125mg/day) following abstention for 30 hours.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Lau and Falk [24] showed evidence of caffeine tolerance following a long period of daily intraperitoneal (ip) drug injections. Development of tolerance has been related to neuroadaptations responsible for withdrawal symptoms when the repeated administration of psychostimulants is discontinued [29,41]. In contrast, it has been shown that an ip injection of caffeine on alternate days for two weeks induces sensitization to its psychomotor stimulation [7,42].…”
Section: Introductionmentioning
confidence: 99%